Automated architectural evaluation of web information systems - Pinto, Felipe; Kulesza, Uirá; Guerra, Eduardo; Maria Júnior, João; Silva, Leo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
Traditional scenario-based architectural analysis methods rely on manual review-based evaluation that requires advanced skills from architects and developers. They are usually applied when the architecture is under development, but before its implementation has begun. The system implementation is one additional and fundamental element that should be used and considered during the software architecture evaluation. In this paper, we propose an approach to add information, which ideally should come from traditional evaluation methods, about scenarios and quality attributes to the source code of web-based systems using metadata. The main aim is to enable the automatic architecture analysis by producing a report with information about scenarios, quality attributes and source code assets, such as: (i) the potential tradeoff points among quality attributes, (ii) the execution time for scenarios and if it has failed or not. Up to now, the approach has been applied mainly to web-based systems, but it can be adapted to other software domains. The paper also presents the tool used to perform static and dynamic analysis, and the results of its application to an e-commerce web system and an enterprise information web system.